Comprehensive treatment outcomes of giant cell tumor of the spine: A retrospective study. Issue 32 (12th August 2022) - Hashimoto, Kazuhiko; Nishimura, Shunji; Miyamoto, Hiroshi; Toriumi, Kensuke; Ikeda, Terumasa; Akagi, Masao
Abstract : There is no consensus on a treatment strategy for spinal giant cell tumor of bone (GCTB) because of the difficulty in their treatment. Treatment options often include the use of the controversial denosumab, an antibody therapy aimed at tumor shrinkage, different curettage techniques, resection, or a combination of these therapies. The current study aimed to identify treatment methods associated with favorable outcomes in patients with spinal GCTB. We retrospectively reviewed 5 patients with spinal GCTB, including patients with tumors of the sacrum, treated at our hospital between September 2011 and November 2020. Two men and 3 women were included in the study. The median follow-up period was 74 months (range: 14–108 months). We surveyed the tumor site, treatment method, denosumab use, and outcomes. The median age was 17 years (range: 17–42 years). There were 2 cases of sacral GCTB and 1 case each of lumbar, cervical, and thoracic vertebral GCTB. The comorbidities observed included hepatitis, malignant lymphoma, atopic dermatitis, and asthma. The treatment method included zoledronic acid after embolization and denosumab, denosumab only, curettage and posterior fusion, and curettage resection after embolization and anterior and posterior fusion. Denosumab was used in all cases. Three patients were continuously disease-free, 1 patient with no evidence of disease, and 1 patient alive with disease. Aggressive treatment, especially surgical treatment, may lead to good results in spinal GCTB.